Sierpinski gasket patch and monopole antenna - Ja'afar, Abd. Shukur (2005)
The use of fractal geometry in designing antenna has been a recent topic of interest. It have already proved that fractal shaped have their own unique characteristics that improved antenna achievement without degrading antenna properties. This dissertation tells about one of familiar geometry in fractal antenna, Sierpinski gasket. Here, two types of antenna are designed: Sierpinski gasket patch and Sierpinski gasket monopole. Maximum iteration that applies to these antennas is three. The behaviors of both type antennas are investigate such as return loss, number of iteration and radiation pattern. Simulation, fabrication and testing have been done. The entire antenna shows multiband in resonant frequencies. For Sierpinski monopole shows a pattern in return loss but not for Sierpinski patch. Monopole type shows the frequency band log-periodically spaced by two, same as the scale factor among the structure (sub-gasket). The self-similarity properties of fractal structure are translated into its electromagnetic behavior.